2021
DOI: 10.1007/s10751-021-01764-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recycled Q235 steel chips from rolling billet scales

Abstract: In the last decades, the demand for steel has increased exponentially generating tons of waste impacting the environment. The most common waste in steelmaking process are slags which are produced during the rolling process of steel billets. This situation has encouraged the scientific community in finding environmentally possible ways to take advantage of this slags. In this work, we present the structural and magnetic properties of solid state recycled Q235 steel chips obtained by powder metallurgy and extrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The information provided in the present work would be very useful for posterior attempts to recycle these types of steel slags. As a matter of fact, recently our research group has reported the reduction of the slags produced in SIDERPERU plant [5] and also our initial achievements in recycling them into Q235 steel pieces [6], for which the information provided in the present work were very useful.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The information provided in the present work would be very useful for posterior attempts to recycle these types of steel slags. As a matter of fact, recently our research group has reported the reduction of the slags produced in SIDERPERU plant [5] and also our initial achievements in recycling them into Q235 steel pieces [6], for which the information provided in the present work were very useful.…”
Section: Resultsmentioning
confidence: 76%
“…The partial replacement of cement by steel slags makes a significant contribution to the steel industry and helps to reduce CO 2 emissions [2]. Thus, finding an appropriate use of steel slags is very important for both, to reduce the potential impact on the environment and to maintain the sustainability of natural resources [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…If these resources are reasonably treated, then not only the environment would be protected and disposal costs reduced, but also proposing new cheap technology for producing advanced materials [3]. Some attempts in re-using waste materials from steel industry includes iron oxide pigments, new metal pieces, manufacturing equipment, chemical tankers, automotive and airplane components [4,5].…”
Section: Introductionmentioning
confidence: 99%